2004
DOI: 10.1124/dmd.104.000349
|View full text |Cite
|
Sign up to set email alerts
|

Effective Dosing Regimen of 1-Aminobenzotriazole for Inhibition of Antipyrine Clearance in Guinea Pigs and Mice Using Serial Sampling

Abstract: ABSTRACT:Single-dose pharmacokinetics of 1-aminobenzotriazole (ABT), a potent nonspecific inhibitor of cytochromes P450 (P450s), were characterized after oral administration to mice and guinea pigs at doses of 50, 100, and 150 mg/kg using serial sampling in both species. Only 30-l blood samples were drawn from jugular veincannulated mice using Microvette capillary tubes containing lithium heparin. A comparison of the pharmacokinetics of antipyrine (AP) administered i.v. at 20 mg/kg to mice followed by serial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 12 publications
3
73
1
Order By: Relevance
“…A summary of antipyrine subcutaneous pharmacokinetics after 2-hour and 24-hour bolus ABT pretreatment is provided in Fig. 1A and Table 1 . Antipyrine was administered by subcutaneous, rather than intravenous, dosing in our experimental design (compared with the report by Balani et al, 2004). Results from a bioavailability (F) study (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A summary of antipyrine subcutaneous pharmacokinetics after 2-hour and 24-hour bolus ABT pretreatment is provided in Fig. 1A and Table 1 . Antipyrine was administered by subcutaneous, rather than intravenous, dosing in our experimental design (compared with the report by Balani et al, 2004). Results from a bioavailability (F) study (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We considered the duration of ABT's inhibitory effect after a single dose. A report by Balani et al (2004), describing the interaction between ABT and antipyrine in mice, indicated clear inhibition of P450 activity to 8 hours postdose; however, low levels of antipyrine were observed at the 24-hour time point. Assuming a constant level of P450 inhibition over 24 hours (and monoexponential elimination of antipyrine), one would have expected much higher antipyrine levels at 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ABT undergoes bioactivation to a reactive intermediate that alkylates most CYPs, resulting in their inactivation (46). Thus, the pretreatment of animals with ABT during a toxicology study (a dose of 50 mg/kg administered 2 h before administration of the test article is a common practice (47,48)) may reduce the severity of adverse events, but only if such events are mediated by a toxic metabolite and not the parent compound itself. This approach has been used to implicate metabolites in the onset of hepatotoxicity in mice following administration of furosemide, (49) and nephrotoxicity in rats following treatment with [2,[3][4][5][6][7][8][9][10][11][12][13][14] C]-N-(3,5-dichlorophenyl)succinimide (50).…”
Section: Animal Models and The Study Of Metabolic Fatementioning
confidence: 99%